1966
DOI: 10.1002/app.1966.070100603
|View full text |Cite
|
Sign up to set email alerts
|

Water–formaldehyde–hydrogen sulfide system. II. Formation and growth of thiomethylenic chains.

Abstract: SynopsisA linear polymer with a high melting point is obtained from the water-formaldehydehydrogen sulfide system in the presence of sulfuric acid. This polymer is substantially formed by a polythiomethylene chain with a few oxymethylene units. Its formation involves a topochemical reaction of the mercaptomethanol present in solution on the first separation solid of the system. On heating, the polymer loses oxymethylene units; in the same way, the first solid product separated from the system loses formaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Melting points reported for poly(thiomethylene) vary widely, presumably reflecting differences in polymer chain length related to different methods of preparation: ca. 80,123-124,160-205,175-176, 220-230, 220-245, 220-248, 220-255, and 245-260 °C have all been reported (56,(58)(59)(60)(61)(62)(63).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Melting points reported for poly(thiomethylene) vary widely, presumably reflecting differences in polymer chain length related to different methods of preparation: ca. 80,123-124,160-205,175-176, 220-230, 220-245, 220-248, 220-255, and 245-260 °C have all been reported (56,(58)(59)(60)(61)(62)(63).…”
Section: Resultsmentioning
confidence: 98%
“…Early studies conducted in Germany in the late 1800s (50-52) indicated that CH2I2 reacts with Na2S in aqueous solution or NaHS in alcohol solution to form the cyclic thioformaldehyde trimer 1,3,5-trithiane [mp 220 °C (53)]: ch2-s sz ch2 \h2V 1,3,5-trithiane This also represents the major product of the reaction of H2S with formaldehyde in aqueous solution under acidic conditions (54). Other polymers identified from the reaction of dihalomethanes or formaldehyde with hydrogen sulfide species include the linear polymer poly(thiomethylene) [HS(CH2S)"H, n > 1] and minor amounts of the cyclic thioformaldehyde tetramer 1,3,5,7-tetrathiocane [mp 48-49 °C (55,56)] and pentamer 1,3,5,7,9-pentathiacyclodecane [mp 120-123 °C (56, 57)], as well as copolymers of poly(oxymethylene) /poly(thiomethylene) (58,59).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our attention is drawn to polythiomethylene, which is prepared from hydrogensulfide and formaldehyde (Scheme 1b). [31] Hydrogen sulfide and formaldehyde can be respectively viewed as the shortest di-thiol compound and the simplest aldehyde. Mechanistically, polythiomethylene is a product from thiol-aldehyde polycondensation.…”
Section: Introductionmentioning
confidence: 99%